Smallholder farmers’ innovation systems in climate-smart agriculture: Interview findings from Tanga Region, Tanzania - Smith, Harriet; Recha, John W.M.; Sallu, Susannah; Whitfield, Stephen; Sayula, George; Mziray, Sylvester; Gaworek-Michalczenia, Marta (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This Info Note summarizes the findings of 228 interviews with smallholder farmers participating in two CSA interventions in Tanga Region, Tanzania. The study examines how agricultural innovation happens in the context of CSA interventions, and explores differentiated experiences of innovation within and across the two case study programs. Through exploring innovation processes, this brief highlights the diversity of actors, approaches and outcomes of CSA interventions, who does and does not benefit, and raises questions about the viability of, and challenges with global ambitions to upscaling CSA.